Effect of dentine surface treatment on leakage of root fillings with a glass ionomer sealer. - Holland, R.; Sakashita, M. S.; Murata, S. S.; Dezan Júnior, Eloi [UNESP] (My University, 1995)
The purpose of this study was to observe the quality of seal of the glass ionomer cement, Ketac-Endo, after treatment of the root canal wall. The root canals of 140 extracted human teeth were prepared biomechanically. The root canals were treated with either EDTA or received an intracanal dressing of calcium hydroxide or camphorated paramonochlorphenol. The root canals were filled by the lateral condensation technique with gutta-percha points and the sealer Ketac-Endo, or zinc oxide-eugenol cement or Sealapex. The teeth were placed into a 2% methylene blue dye solution inside a flask, which was attached to a vacuum pump. Leakage was measured linearly. Sealapex exhibited significantly less leakage than Ketac-Endo or zinc oxide-eugenol cement (P<0.01). The use of EDTA and intermediary dressings reduced significantly (P<0.01) the leakage observed with the zinc oxide-eugenol sealer and Ketac-Endo.
Keywords: 4 chlorophenol; 4-chlorophenol; biomedical and dental materials; calcium hydroxide; chlorophenol; edetic acid; glass ionomer; Ketac Endo; root canal filling material; salicylic acid derivative; sealapex; zinc oxide eugenol; comparative study; endodontics; evaluation; human; methodology; tooth disease; Calcium Hydroxide; Chlorophenols; Dental Leakage; Edetic Acid; Evaluation Studies; Glass Ionomer Cements; Humans; Root Canal Filling Materials; Root Canal Irrigants; Root Canal Obturation; Salicylates; Zinc Oxide-Eugenol Cement